The art and science of personality development - McAdams, Dan P. (New York : The Guilford Press, 2015)
"Integrating state-of-the-art personality and developmental research, this book presents a new and broadly integrative theory of how people come to be who they are over the life course. Preeminent researcher Dan P. McAdams traces the development of three distinct layers of personality--the social actor who expresses emotional and behavioral traits, the motivated agent who pursues goals and values, and the autobiographical author who constructs a personal story for life. Highly readable and accessible to scholars and students at all levels, the book uses rich portraits of the lives of famous people to illustrate theoretical concepts and empirical findings"--
"This book is for anybody who has ever asked psychological questions like these: Who am I? How did I become the person I am today? My goal in this book is to tell a compelling story about personality development as it plays out in individual human lives across the human life course. It is a story that recognizes the artistry of individual lives while examining what contemporary science has to tell us about how human lives are psychologically patterned and how these patterns develop over time. I draw upon many of the most illuminating studies and intriguing ideas in psychological science today to describe and explain the development of human personality over the life course. Reflecting the three central metaphors in my theory of personality development, the book is divided into three parts - Becoming the Social Actor, Becoming the Motivated Agent, and Becoming the Autobiographical Author. In the three sections, I move back and forth across the life span to sketch out a full psychological portrait of human personality and trace its development from birth through old age"--
I. Becoming an Actor -- 1. In the Beginning. -- 2. The Actor Enters the Stage: How We Perform Emotion -- 3. The Problem of Self-Regulation -- 4. The Actor Grows Up: How Traits Develop into Adulthood -- II. Becoming an Agent -- 5. The Age 5-7 Shift -- 6. The Motivational Agenda: What Agents Want -- 7. How Values Shape Agency: Morality, Religion, and Politics -- III. Becoming an Author -- 8. The Stories We Live By -- 9. Generative Lives, Redemptive Life Stories -- 10. The Sense of an Ending.
Includes bibliographical references (pages 321-352) and index.
Keywords: Personality; Social psychology